The innocent Id: A psychoanalytic exploration of Jenny Curran’s unconscious desires in Forrest Gump (1994) film - Dewanti, Azzahra Safira; Kurniawan, Fitri (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This study examines the psychological complexity of Jenny Curran in Forrest Gump (1994) through a psychoanalytic lens, focusing on how unconscious desires influence her actions and relationships. Using Sigmund Freud’s concept of the Id, Ego, and Superego, the research explores the impact of childhood trauma and societal expectations on her self-destructive tendencies. A qualitative approach was employed, utilizing content analysis of key scenes that depict Jenny’s psychological struggles. Primary data includes dialogues, behaviors, and pivotal moments in the film, while secondary sources comprise psychoanalytic theory and literature on trauma and gender representation. The study interprets Jenny’s decisions through the tension between impulsive desires and moral reasoning, revealing that Jenny’s behavior is largely controlled by the Id, which seeks immediate gratification and escape from emotional distress. However, her Ego mediates between these desires and external reality, while her Superego reinforces guilt and internalized moral constraints. This psychological conflict shapes her unstable relationships, particularly with Forrest, as she alternates between seeking love and rejecting emotional security. Her journey illustrates the lasting effects of unresolved trauma and the unconscious forces that dictate human behavior. By analyzing Jenny’s character, this research enhances the understanding of female character development in film through psychoanalysis. It demonstrates how cinematic narratives depict internal struggles, offering insights into the portrayal of women’s experiences in media. Furthermore, it contributes to discussions on trauma, identity, and psychological depth in film storytelling, highlighting the role of unconscious motivations in shaping characters arcs. These findings underscore the significance of psychoanalytic film analysis in understanding how past trauma influences characters’ actions and relationships, providing a deeper perspective on the psychological complexities of female figures in films.